Kontroversi Pembakaran Bendera Tauhid: (Studi Atas Pemberitaan Kompas.com dan Republika.co.id) - Anna Sofiana; Anwari Anwari; Ahmad Khoirul Fata (LPPM IAIN Sultan Amai Gorontalo, 2020)
The burning of Tawhid flag in Garut, on October 2018, caused a pro-cons reaction in the society. A number of mass media reported it, including two mainstream media: kompas.com and republika.co.id. Both online media have contracted and framed the news of the event according to their ideologies. Using the framing analysis of the Zongdang Pan and Gelarld M. Kosicki, this article tries to uncover the framing of the two new media for the occasion of burning the tawhid flag. From this study, it can be concluded that the framing of Kompas.com is promoting nationalist value by demonstrating the actions and arguments of several public officials in addressing the flag burning incident. Kompas.com try to be neutral by not mentioning vulgar flag name and not giving accusations against any party. While the framing done by Republika.co.id still shows its alignments towards Islam. Republika.co.id often refer to the word ' Tawhid ' as the name of a flag with the use of the word